Respostas locais e sistêmicas induzidas por endotoxina em Piaractus mesopotamicus (Holmberg, 1887) tratados com cromo - Flores Quintana, Carolina [UNESP] (2002)
This work had for objectives to evaluate the response systemic induced by the injection intraperitoneal of 3,0 mg/kg of lipopolissacharideo (LPS) of Escherichia coli and the eventual effects of the alimentary supplementation with mixed trivalent chromium to the ration. Were used three hundred fish Piaractus mesopotamicus (Holmberg, 1887), weighing 80 g on average.; distributed in 20 aquariums and five treatments, which are a group control, non supplemented and that didn't receive LPS; a group that received only LPS and other three, CRa, CRb and CRc that received LPS and two, four six parts for millions of trivalent chrome in the ration. Material for haematocrit determination, concentration cortisol plasmático and glucose, concentration of hepatic glycogen, index hepatosomático and modifications in the branchial structure were appraised by histology picked before and a, two, four, nine, 14, 19 and 24 days after the injection of LPS. The experimental design was randomized entirely, in a 5 x 8 factorial. The results demonstrated that the levels of circulating cortisol increased in all the groups as well as there was increment of the stock of hepatic glycogen. The haematocrit didn't present significant difference and the gills presented quick structural modifications